Observation of medium-induced yield enhancement and acoplanarity broadening of low-𝑝T jets from measurements in 𝑝⁢𝑝 and central Pb-Pb collisions at √𝑠NN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physical review letters, 2024)
The ALICE Collaboration reports the measurement of semi-inclusive distributions of charged-particle jets recoiling from a high transverse momentum (high 𝑝T) hadron trigger in proton-proton and central Pb-Pb collisions at √𝑠NN=5.02 TeV. A data-driven statistical method is used to mitigate the large uncorrelated background in central Pb-Pb collisions. Recoil jet distributions are reported for jet resolution parameter 𝑅 =0.2, 0.4, and 0.5 in the range 7<𝑝T,jet<140 GeV/𝑐 and trigger-recoil jet azimuthal separation 𝜋/2<Δ⁢𝜑<𝜋. The measurements exhibit a marked medium-induced jet yield enhancement at low 𝑝T and at large azimuthal deviation from Δ⁢𝜑∼𝜋. The enhancement is characterized by its dependence on Δ⁢𝜑, which has a slope that differs from zero by 4.7⁢𝜎. Comparisons to model calculations incorporating different formulations of jet quenching are reported. These comparisons indicate that the observed yield enhancement arises from the response of the QGP medium to jet propagation.